Agile software development teams: Communication, shared values, growth and improvements through demographic and contextual factors - Lukić-Nikolić Jelena; Lazarević Snežana; Antić Sunčica (Journal of Engineering Management and Competitiveness)
This paper investigates how demographic factors (gender and age), and contextual factors (length of team membership and work type) affect communication, shared values, collaborative growth and improvements in agile software development teams in Serbia. Empirical research was conducted using a specially designed online questionnaire which consisted of profile questions and three highly reliable scales focusing on agile software development team communication, shared values, and collaborative growth and improvements. In the period from April to October 2024, a total of 107 agile software development team members from Serbia participated in the research. Data analysis was conducted using descriptive statistics, the Mann-Whitney U-test, and the Kruskal-Wallis H-test. The findings reveal no statistically significant differences in communication, shared values, or collaborative growth based on age, length of team membership, and work type. However, a notable gender difference was observed, with female team members reporting a higher level of agreement on shared values within their teams. These results underscore the critical role of gender dynamics in fostering a cohesive team environment in agile settings. Understanding these dynamics is essential for enhancing team collaboration and performance, suggesting that organizations should consider gender inclusivity when developing agile software development teams.